Biomechanical Comparison of Achilles Tendon Pullout Strength Following Midline Tendon-Splitting and Endoscopic Approaches for Calcaneoplasty. (October 2019) - Michalski, Max P.; Gonzalez, Tyler A.; Metzger, Melodie F.; Nelson, Trevor J.; Eberlein, Samuel; Pfeffer, Glenn B.
Background: Calcaneoplasty is a common procedure performed for the management of Haglund's syndrome when nonoperative management fails. Midline tendon-splitting and endoscopy are 2 common approaches to calcaneoplasty. Studies have suggested that an endoscopic approach may allow earlier return to activity and superior outcomes, but there are no biomechanical or clinical studies to validate these claims. The goal of this study was to quantify and compare Achilles tendon pullout strength following midline tendon-splitting and endoscopic calcaneoplasty in cadaveric specimens. Methods: Twelve match-paired cadaveric specimens were randomly divided into 2 groups: endoscopic and midline tendon-split. Following calcaneoplasty, fluoroscopy was used to match bone resection and the Achilles was loaded to failure in a mechanical testing system. A paired-samples t test was conducted to compare bone resection height, bone resection angle, load to failure, and mode of failure. Results: The endoscopic approach yielded a 204% greater postsurgical pullout strength for the Achilles tendon than the midline tendon-split (1368 ± 370 N vs 450 ± 192 N, respectively) ( P < .05). There were no differences in resection angle or resection height. All specimens failed due to bone or tendon avulsion. Conclusion: Endoscopic calcaneoplasty had more than 3 times greater pullout strength than the midline tendon-splitting approach. Clinical Relevance: This may allow earlier return to functional rehabilitation following endoscopic calcaneoplasty, but further studies are needed to determine if these differences are clinically significant. Further understanding of the time-zero biomechanics following calcaneoplasty may provide guidance regarding postoperative management with respect to surgical approach.